The effect of oral administration of monosodium glutamate on epileptogenesis in infant rats - YANANLI, HASAN RACİ (JOHN LIBBEY EUROTEXT LTD, 2020)
Aim. Glutamate is an excitatory neurotransmitter that is widely distributed throughout the brain. An increase in glutamate concentration or sensitivity of glutamate receptors triggers neurodegenerative diseases, epilepsy in particular. Monosodium glutamate is a substance added to foods to enhance flavour. We investigated the effect of monosodium glutamate on epileptogenesis, as well asheight and weight, in rats that were just weaned. Methods. Twenty-four male and female 21-day-old Wistar Albino rats were divided into two groups: one with monosodium glutamate added to the drinking water, and a control in which NaCl was added to the drinking water. The electrical stimulation threshold values were determined in animals to which the hippocampal kindling process was applied, and the stimulations at these threshold values were invariably applied to the animals until they were kindled. Results. The electrical stimulation threshold values of the monosodium glutamate group did not statistically change, whereas the number of required stimulations for kindled rats was significantly lower compared with the control group. Conclusion. These results reveal that long-term oral administration of glutamate salts causes an increase in excitability in the central nervous system during ontogenetic development.
Keywords: epilepsy; glutamate; hippocampus; kindling; ELECTRICAL-STIMULATION; OXIDATIVE STRESS; DIET; SEIZURE; OBESITY